2012
DOI: 10.9790/1684-0240106
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lime on the Compaction and Strength Behaviour of Red Earth treated with Mine tailings

Abstract: Mine tailings is an industrial by-product obtained from mining industry. The effective disposal of mine tailings(MT) is a great challenge to both civil engineers and mining engineers. On the other hand red earth(RE) is a non expansive soil which is having kaolinite as primary clay mineral and it is a natural soil available in vast areas of India, and also in Karnataka. In the present investigation an attempt has been made to improve the engineering properties of red earth by using mine tailings. The mine taili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Laterites are characterized by low swell potential, low shrinkage and high density when compacted at optimum water content. Previous studies on laterites showed that some of their properties can be improved upon by using materials such as blast furnace slag, iron ore waste, tincal ore waste, fly ash, waste wood ash, mine tailings, rice husk ash, coal waste, bagasse ash, and sugar cane straw (Kula et al, 2002;Osinubi & Eberemu, 2009;Ramesh et al, 2012;Hamdi and Srasra, 2013;Roy, 2013;Etim, 2015;Oluremi, 2015;Umar et al, 2015;Modarres & Nosoudy, 2015;Umar et al, 2016). Several research groups have reported that using alternative supplementary cementitious materials (SCMs) to upgrade the properties of soils could reduce construction cost and enhance the performance of hydraulic barrier systems (Yeheyis et al, 2010;Ilić et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Laterites are characterized by low swell potential, low shrinkage and high density when compacted at optimum water content. Previous studies on laterites showed that some of their properties can be improved upon by using materials such as blast furnace slag, iron ore waste, tincal ore waste, fly ash, waste wood ash, mine tailings, rice husk ash, coal waste, bagasse ash, and sugar cane straw (Kula et al, 2002;Osinubi & Eberemu, 2009;Ramesh et al, 2012;Hamdi and Srasra, 2013;Roy, 2013;Etim, 2015;Oluremi, 2015;Umar et al, 2015;Modarres & Nosoudy, 2015;Umar et al, 2016). Several research groups have reported that using alternative supplementary cementitious materials (SCMs) to upgrade the properties of soils could reduce construction cost and enhance the performance of hydraulic barrier systems (Yeheyis et al, 2010;Ilić et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Ramesh, Krishnaiah and Supriya [7] studied that the addition of various percentage of lime to the Red Earth treated with optimum percentage of mine tailings. Mine tailings was collected from an open dump from Kolar Gold Fields (KGF).…”
Section: Introductionmentioning
confidence: 99%